Cost and Reliability Optimization Strategy of PV-Diesel Hybrid System: Case Study of Legon Bajak Diesel Power Plant, Karimun Jawa - Saputra, M. Ramadhan; Sambegoro, Poetro Lebdo (ITB Graduate School Conference, 2025)
Karimun Jawa, as an archipelago, still relies on diesel power plant as the main source of electricity which causes high production costs and the risk of supply instability due to fuel distribution barriers. This study aims to design and optimize a hybrid power generation system combining solar PV, diesel power plant, and batteries to lower the cost of electricity supply and improve supply reliability at Legon Bajak diesel power plant. The approach used involves technical simulation with PVSyst to assess the performance of the solar power plant and economic analysis using HOMER Pro on three system scenarios: Existing diesel generator, PV-Diesel, and Hybrid PV-Diesel. Based on load data from field surveys and irradiation data from NASAPOWER, the Diesel-PV-Battery scenario proved to be the most optimal with a solar power plant capacity of 5,072 kWp and 13,570 kWh batteries, capable of producing 5.69 GWh per year, reducing fuel consumption by 82.6%, and reducing LCOE from Rp4,907/kWh to Rp3,524/kWh. Economically, the system demonstrates feasibility with an IRR of 15.9%, ROI of 11.5%, and investment payback period of 5.56 years, making it a technically and economically viable solution to support clean energy transition in remote areas such as Karimun Jawa.